Chronic Thromboembolic Pulmonary Hypertension: Epidemiology, Diagnosis, and Management. Issue 2 (March 2018) - Yandrapalli, Srikanth; Tariq, Sohaib; Kumar, Jessica; Aronow, Wilbert S.; Malekan, Ramin; Frishman, William H.; Lanier, Gregg M.
Abstract : Chronic thromboembolic pulmonary hypertension (CTEPH), classified as World Health Organization (WHO) group 4 pulmonary hypertension (PH), is an interesting and rare pulmonary vascular disorder secondary to mechanical obstruction of the pulmonary vasculature from thromboembolism resulting in PH. The pathophysiology is complex, beginning with mechanical obstruction of the pulmonary arteries, which eventually leads to arteriopathic changes and vascular remodeling in the nonoccluded arteries and in the distal segments of the occluded arteries mediated by thrombus nonresolution, abnormal angiogenesis, endothelial dysfunction, and various local growth factors. Based on available data, CTEPH is a rare disease entity occurring in a small proportion (0.5–3%) of patients after acute pulmonary embolism with an annual incidence ranging anywhere between 1 and 7 cases per million population. It is often underdiagnosed or misdiagnosed as idiopathic pulmonary arterial hypertension due to a lack of clinical suspicion or the under-utilization of radionuclide ventilation/perfusion scan. Although the current standard remains planar ventilation/perfusion scintigraphy as the initial imaging study to screen for CTEPH, and invasive pulmonary angiography with right heart catheterization as confirmatory modalities, they are likely to be replaced by modalities that can provide both anatomic and functional data while minimizing radiation exposure. Surgery is the gold standard treatment and offers better improvements in clinical and hemodynamic parameters compared with medical therapy. The management of CTEPH requires a multidisciplinary team, operability assessment, experienced surgical center, and the consideration of medical PH-directed therapies in patients who have inoperable disease, in addition to supportive therapies. Although, balloon pulmonary angioplasty is gaining interest to improve pulmonary hemodynamics and symptoms in CTEPH patients not amenable to surgery, further investigative randomized studies are needed to validate its use. It is very important for the present-day physician to be familiar with the disease entity and its appropriate evaluation to facilitate early diagnosis and appropriate management.